(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Sahgal has first-hand knowledge of politics and political figures in India, for she spent most of her childhood in Anand Bhawan, the ancestral home of the Nehrus in Allahabad. It is beyond doubt that politics is in her blood. Jawaharlal Nehru was her mother’s brother, while her father died because of an illness he suffered in prison when he was jailed for participating in India’s freedom struggle. The important political events form the background for each of her novels.